Demographic Perspectives and De-escalation Challenges in Pediatric Emergency Care for Children with Special Health Care Needs - Ninoshka Rivera-Koberstein; Amit Agrawal; Sagar Galwankar (Journal of Emergencies, Trauma and Shock)
Introduction: Medical literature on emergency care for children with special healthcare needs (SHCNs) reports the inherent challenges in the managing of these children, like limited history, distress for patients and families, and unique management requirements for healthcare teams. This study analyzed the demographic data on children with SHCNs to explore de-escalation strategies, the effectiveness of chemical de-escalation, and clinical management strategies used and compared the length of stay in the emergency department (ED) between patients who received medications and those who did not. Methods: This was a retrospective and cross-sectional study. Data were collected from the last 150 patients diagnosed with SHCNs across three ED s within this hospital system since July 1, 2023. Children aged 18 years or younger diagnosed with SHCNs requiring special modifications. Chi-square test, Mann–Whitney U-test, and Kruskal–Wallis H-test. Results: The demographic analysis showed that 60% of children with SHCNs were female, with a mean age of 12.3 years. The most common presentation time was 6–8 pm. autism spectrum disorder (28%) and anxiety disorder (27%) were the most frequent diagnoses, with substance abuse present in 45% of patients. Medications helped reduce the ED stay, which was statistically significant, suggesting that medications may facilitate effective de-escalation; At the same time, in a few cases, verbal de-escalation also appeared helpful. There is a need for robust documentation on verbal de-escalation strategies, such as details on patients who did not receive medications and were successfully managed verbally or required repeated reassurance. Conclusions: This study provides insight into the diverse challenges of managing children with SHCNs in the emergency settings. The high prevalence of substance abuse, particularly in children with autism spectrum, increases the complexity of care. While medications may reduce ED stay, further research is needed to understand this patient population’s complex needs better.